2011
DOI: 10.1159/000338895
|View full text |Cite
|
Sign up to set email alerts
|

Giant Encephalocele: A Study of 14 Patients

Abstract: Background: Giant encephalocele is a rare condition and few published reports are available in the English literature. It is a challenge to neurosurgeons, even today. This series consists of 14 patients with giant encephaloceles treated at our institute. Material and Observation: Over a period of 8 years, from 2002 to 2009, 110 patients with encephaloceles were managed at our institute. Amongst them, 14 were children with giant encephaloceles. All patients had CT/MRI or both prior to surgery, and all were oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
88
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(89 citation statements)
references
References 16 publications
0
88
0
1
Order By: Relevance
“…Anterior encephalocele are more common in male but posterior encephalocele are commonly seen in females. On review of literature, we found a single case series of giant encephalocele [1]. Hydrocephalus with giant occipital encephalocele is very rare.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Anterior encephalocele are more common in male but posterior encephalocele are commonly seen in females. On review of literature, we found a single case series of giant encephalocele [1]. Hydrocephalus with giant occipital encephalocele is very rare.…”
Section: Discussionmentioning
confidence: 93%
“…Hydrocephalus with giant occipital encephalocele is very rare. In Mahapatra series only one neonate with occipital giant encephalocele had hydrocephalus out of three cases [1]. Magnetic resonance imaging of Brain is the investigation of choice in these cases.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations